DIGITAL CAPITAL MARKET OPERATIONS: A LITERATURE REVIEW - Harshith B (International Journal of Research -GRANTHAALAYAH, 2025)
An immense amount of change, development and improvement in the performance of capital market due to the advancement in the technology and its use in daily transactions in worldwide economies. This research paper aims to present an overview about the digital operations conducted in capital markets. The study is descriptive research in nature, it employs the descriptive research approach that is suitable in reviewing the available literature in order to gain an insight into the digitalization process and the digital operations taking place in Indian capital markets. The output of the study indicates that digitalization is widely adopted in capital markets in order to facilitate the daily transaction taking place in such markets. Further, research indicates that new investment tools are presented in the capital market with the help of digitalization and technology. Research also indicates that the threat of disruption, acquiring and retaining digital talent and the innovation are considered major challenges for the digital operations in capital markets. While investigating the opportunities in front of digital capital market operation, they include assets inflow, expanding products offering, improved technology and data mining and globalization, such opportunities can contribute towards the development of the financial markets’ performance. Regardless of the opportunities that exist in front of the digital capital market operation, there are also tremendous challenges that hinder the performance of digital capital market operation. This requires policy makers to investigate the chances of developing the technological infrastructure so as to facilitate the performance of digital capital market operations.